Difference of Physical Education Teachers Skills viewed from Students Creative Thinking Skills - Basuki Basuki; Yudi Dwi Saputra; Ilmul Ma’arif; Aditya Harja Nenggar (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to determine the teacher's skills in teaching in terms of students' creative thinking skills. Physical education goals which contain the intellectual, mental, social and emotional dimensions and the use of curriculum 13 as the vehicle to achieve that goal. Curriculum 13 to achieve that goal suppresses 4C namely critical, creative, collaborative and communicative. This type of quasi-experimental research uses a comparative causal design. The study population was all eighth grade students in State Middle School 1 Diwek and MTS State 15 Jombang. The sampling technique in this study used random sampling of classes, a sample of 64 students. Data collection of this study uses the sheet of teaching skills and test thinking of students. The data in this study were analyzed using SPSS 20 and used a significance level of 0.05. The skills of physical education teachers can be seen the teacher's picture in conditioning during the learning process. Based on the results obtained by the PJOK teacher data in SMP N Diwek 1, the score was 83.33%. Whereas physical education teachers at MTs N 15 Jombang get a value of 70% and data analysis shows that the probability value is less than 0.05 which is equal to 0,000 so that the null hypothesis can be withdrawn rejected and the research hypothesis accepted. This means that there are differences in physical education teacher skills in SMP N Diwek 1 with physical education teachers in MTs N 15 Jombang in terms of creative thinking of students.